Anti-inflammatory activity of gel containing novel elastic niosomes entrapped with diclofenac diethylammonium - A. Manosroi (2018)
The objective of this study was to develop a novel elastic bilayer vesicle entrapped with the non-steroidal anti-inflammatory drug (NSAID), diclofenac diethylammonium (DCFD) for topical use. Eighteen bilayer vesicular formulations composing of DPPC or Tween 61 or Span 60 mixed with cholesterol (at 1:1, 3:7 and 1:1 molar ratios, respectively) and ethanol at 0-25% (v/v), by chloroform film method with sonication were developed. The elastic Tween 61 niosomes which gave no sedimentation, no layer separation, unchanged particle sizes (about 200 nm) were selected to entrap DCFD. The entrapment efficiency of the drug in the conventional and elastic Tween 61 niosomes was 65 and 93%, respectively. At least 87% of DCFD determined by HPLC remained in elastic Tween 61 niosomes when kept at 4, 27 and 45 °C for 3 months. The deformability index values of the elastic niosomes were 13.76 and 3.44 times higher than the conventional niosomes entrapped and not entrapped with the drug, respectively, indicating the higher flexibility of the elastic vesicle especially, when entrapped with the drug. Transdermal absorption through excised rat skin was performed by vertical Franz diffusion cell at 32 ± 2 °C for 6 h. Gel containing elastic niosomes exhibited fluxes of DCFD in the stratum corneum (SC), deeper skin layer (viable epidermis and dermis, VED) and receiver chamber at 191.27 ± 9.52, 16.97 ± 2.77 and 3.76 ± 0.54 μg/(cm2h), whereas the commercial emulgel, containing an equivalent DCFD, gave 60.84 ± 13.63, 7.33 ± 1.70 and 0.14 ± 0.01 μg/(cm2h), respectively. The in vivo anti-inflammatory activity was evaluated by ethyl phenylpropiolate (EPP)-induced rat ear edema (n = 3). DCFD entrapped in the developed elastic niosomes and incorporated in gel gave the same ear edema inhibition percentages of 23.81% at 30 min, but 2 and 9 times more inhibition percentages at 45 and 60 min than the commercial emulgel, respectively. This result has not only demonstrated the enhancement of transdermal absorption through rat skin, but also the in vivo anti-inflammatory effect of DCFD when entrapped in the developed novel elastic Tween 61 niosomes, as well. © 2008 Elsevier B.V. All rights reserved.